2019
DOI: 10.5897/ijwree2019.0855
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sand-dam water quality and its suitability for domestic use in arid and semi-arid environments: A case study of Kitui-West Sub-County, Kenya

Abstract: Sand dams are one of the most successful rainwater harvesting methods, adopted in most of arid and semi-arid lands (ASALs) of Kenya to secure domestic water supply and micro-irrigation. Their ability to maintain acceptable water quality, under extreme climatic conditions of recurrent drought and floods, is therefore of paramount public health concern as various pollutants find easily their way into them. This study assessed the suitability of sand-dam water abstracted via scoop holes (SCHs) and shallow wells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
2
11
4
Order By: Relevance
“…Total hardness levels should not exceed 300 ppm in drinking water WHO (2011). Moïse et al (2019) found mean TH to be 277.38 mg/L. Whilst a maximum hardness of 1,115 mg/L was recorded, 92% of samples complied with WHO recommendations.…”
Section: Other Physicochemical Parametersmentioning
confidence: 70%
See 4 more Smart Citations
“…Total hardness levels should not exceed 300 ppm in drinking water WHO (2011). Moïse et al (2019) found mean TH to be 277.38 mg/L. Whilst a maximum hardness of 1,115 mg/L was recorded, 92% of samples complied with WHO recommendations.…”
Section: Other Physicochemical Parametersmentioning
confidence: 70%
“…The majority of papers found a similar proportion of samples falling below quality standards. All studies recorded some samples of high to very high risk, except for Moïse et al (2019) whose TDS samples all fell below 1,200 mg/L (marginal)indicating minimal risk. Quinn et al (2018a) tested EC at 50 dam sites with many pump wells and scoop holes tested twice, improving the reliability of results.…”
Section: Electrical Conductivitymentioning
confidence: 98%
See 3 more Smart Citations